Duodenal neuroendocrine tumour associated with minimal change glomerulonephritis. Issue 8 (30th August 2019) - Montague, Emily; Hockenhull, Kimberley; Lamarca, Angela; Al-Sayed, Tamer; Hubner, Richard A
Abstract : Paraneoplastic glomerular disease is an increasingly well-recognised entity, and a wide range of both solid and haematological malignancies have been implicated. The most common glomerular disease associated with cancer is membranous nephropathy. Only a few case reports have described an association between neuroendocrine tumours (NETs) and glomerulonephritis and only one paediatric case in relation to minimal change disease. A 76-year-old woman with a well-differentiated duodenal NET presented with nephrotic syndrome and renal biopsy was suggestive of minimal change glomerulonephritis. Standard therapy with corticosteroids brought little benefit, but a dramatic improvement was seen following initiation of systemic anticancer therapy with lanreotide, a somatostatin analogue. Less than 1 month after initiation of lanreotide, the patient was no longer in a nephrotic state, and after a further 2 months of follow-up had shown no sign of relapse.